Impact of green banking strategies on customer satisfication : a case of commercial banks in Zimbabwe - Demera, Edwin (Midlands State University, 2020)
The research investigated the impact of green banking strategies on customer satisfaction, using a case of commercial banks in Zimbabwe. The research objectives were to: assess the impact of internet banking on commercial bank customer satisfaction, determine the impact of mobile banking on commercial bank customer satisfaction, evaluate the impact of telephone banking on commercial bank customer satisfaction and determine the impact of ATM banking on commercial bank customer satisfaction. The positivism philosophy was assumed and a causal research design was adopted. The target population comprised of 130 commercial bank customers in the Harare central business district. Convenience sampling was used to draw a sample of 104 bank customers based on the Raosoft sample size calculator. Questionnaires were used to collect primary data. Secondary data was drawn from journals, articles, books and websites. 104 questionnaires were administered on an on-spot basis and the response rate was 100%. Descriptive statistics and regression analysis were used to analyse the responses of the bank customers. Solanki (2018) unveiled that internet banking had a positive impact on customer satisfaction. Gomachab and Maseke (2018) revealed that mobile banking had a positive impact on customer satisfaction. Asad et al (2016) found that telephone banking had a positive impact on customer satisfaction. Tadesse (2018) found that ATM banking enhanced customer satisfaction. The findings of the study are: internet banking has a very weak positive impact on customer satisfaction, mobile banking has a weak positive impact on customer satisfaction, telephone banking has a very weak positive impact on customer satisfaction, and ATM banking has a very weak positive impact on customer satisfaction. The study concluded that: provision of banking services on the internet-related channels positively influences customer satisfaction to a less extent, use of mobile applications and USSD short codes positively influences customer satisfaction to a low extent, availability of banking services over the phone positively influences customer satisfaction to a less extent, and use of ATMs by commercial bank customers positively influences their overall satisfaction to a less extent. The study recommends banks to: incorporate the critical factors determining customer satisfaction into their internet banking, educate their customers about internet banking, improve the quality of their mobile banking services so as to increase customer satisfaction, and ensure that there ATMs are always up and running. The suggested areas of further research are: a study of the actual factors affecting satisfaction of commercial bank customers with green banking and investigation into the impact or role of green banking strategies from a qualitative point of view.